Production behavior and efficiency analysis of paddy farm in granary areas of Peninsular Malaysia - Lira Mailena, (2015)
Increasing paddy production through improvement on the paddy yield is the substantial effort to achieve the self-sufficiency level at 70 percent of local consumption by 2020 and Ministry of Agriculture and Agro-based Industry (MoA) of Malaysia set the national paddy yield target at 10 t/ha. Emphasis is focused in eight granary areas of Peninsular Malaysia that are potentially able to achieve the paddy yield target since these granary areas are designated as the main producing center of paddy in Peninsular Malaysian,whereas government supports in production are focused in these areas. Despite various government supports, paddy production is hampered by the lower paddy yield compared to the yield target. In 2008-2013, the average national paddy yield was roughly 3.9t/ha and the average paddy yield in the granary areas varied between 2.96 t/ha and 5.74 t/ha. In same period, national paddy yield grew at 1.30 percent only and the paddy yield growth in the granaries was not more than 10 percent over year. Since at a current technology, the yield is normally associated with the input use, the low paddy yield and slow growth of paddy yield was potentially caused by the technical inefficiency in the input use. The incentive to use more input is constrained by the input prices when policy instruments and subsidies for domestic industry including paddy farms should be reduced as expected in the trade liberalization. In this condition, how the farmer’s response to the change of input prices principally inflames the incentive to use input in paddy production. Besides, Guaranteed Minimum Price (GMP) and price support program that reflected in the paddy price, are other important support to encourage farmers to increase the paddy production. However, to the best of our knowledge, not many estimates on the response of paddy supply to the paddy prices and the response of input demand to the input prices have been reported while the production efficiency depends on this behavior. Therefore, this study generally aims to analyze the production behavior and the efficiency of paddy farms in granary areas of Peninsular Malaysia. The specific objectives are (1) to estimate the production behavior of paddy farm in terms of input demand and output supply elasticity, production elasticity and return to scale, (2) to measure the technical and scale efficiency of paddy farm based on the parametric (stochastic frontier analysis) and nonparametric approaches (DEA and bootstrapped DEA) in order to depict more holistic feature of paddy farms efficiency in Peninsular Malaysia, and (3) to determine factors affecting the technical efficiency of paddy farm based on farmer’s characteristics. Duality theory with restricted transcendental profit function was utilized as it was able to depict the behaviour of input demand and output supply simultaneously. Stochastic Frontier Analysis and Data Envelopment Analysis improved by bootstrapping method were used to measure the level of technical and scale efficiency. In addition, this study used the Tobit model whereas the technical efficiency scores were regressed upon the farmer’s characteristics that could explain variation on the technical efficiency. The findings of this study show that output supply of paddy in most of granary areas (MADA, IADA Pulau Pinang, KADA, IADA KETARA, IADA Kerian Sungai Manik and IADA Barat Laut Selangor) was responsive to the changes of paddy prices and indicated that price support program was effectively encouraging farmers to increase the production. Responsiveness of input demand to its price varied across granary areas and the input demands mostly, were not elastic to the changes of its price. Regarding the result of technical efficiency measurement, paddy farms were not fully technically efficient since the average technical efficiency scores were lower than one. Based on parametric (SFA) and nonparametric (DEA) approaches, the average efficiency scores ranged between 0.42 and 0.69 and suggested that paddy production could be increased by 58 percent of the current production. In addition, out of eight granary areas,paddy farms in IADA Barat Laut Selangor were the most technically efficient farms. However, after correcting the bias in the bootstrapping technique, bias corrected technical efficiency scores were lower than DEA and SFA efficiency scores and paddy farms in those areas should increase the production by 69.5 percent of the current output to achieve the potential production. Hence, bootstrapping technique proved that technical efficiency scores from both approaches were overestimated. In addition, the average of scale efficiency scores were higher than technical efficiency scores and it suggested that inefficiencies were mostly due to inefficient technical practices in the input use rather than the scale of production. Therefore, production increase by improving technical efficiency of paddy farms could be gained by the optimal utilization of production inputs mainly the seed and fertilizer use. In this context, an extension program with regards to the optimal level of seed and fertilizer on the best farm practices should be emphasized. Besides, experienced farmers in IADA Pulau Pinang, Kerian Sungai Manik and Seberang Perak could be the benchmark for other farmers in this area and it would be helpful for setting targets and finding weaknesses of current practices. Courses and trainings could be emphasized for farmers in KADA and IADA Kerian Sungai Manik as this eventswere helpful to share the knowledge and information on the best farm practices.